Evaluation of a latex agglutination test for Clostridium difficile in two nursing home outbreaks. - Bennett, R G (1989)
The Culturette Brand Clostridium difficile test (CDT; Marion Laboratories, Inc., Kansas City, Mo.) is a latex agglutination test for C. difficile. The recent controversy involving the identity of antigens detected by CDT has made decisions on its use difficult. We compared the test results with those of selective culture and stool cytotoxin assays in investigations of two nursing home outbreaks of C. difficile-associated disease in order to formulate usage recommendations. Selective culture for C. difficile identified 27 (19%) of 142 subjects as carriers. CDT and the stool cytotoxin assay identified only 52 and 48% of these carriers, respectively. Compared with the stool cytotoxin assay, CDT had a high sensitivity (92%) and specificity (89%) for the detection of C. difficile disease, but the positive predictive value of the test was only 17% when the prevalence of disease was 2%. We conclude that the CDT should not be used to identify carriers but that it is a sufficiently sensitive and specific screening test for diagnosing C. difficile disease. However, since the positive predictive value of the CDT is low when the prevalence of disease is low, positive test results should be confirmed by the stool cytotoxin assay.